Life cycle assessment dan keberlanjutan ekonomi-lingkungan produksi bioetanol dari kulit pisang kepok kuning: Systematic review - Putri Ramadan Lazuardi; Aceng Ruyani; M. Lutfi Firdaus (Papanda Publisher, 2026)
This study synthesizes recent findings on the environmental and economic sustainability of banana peel-based bioethanol production using a Life Cycle Assessment (LCA) approach. The utilization of yellow kepok banana peel waste offers significant opportunities to support clean energy transition and sustainable waste management in Indonesia. This research employs a Systematic Literature Review (SLR) method, analyzing 15 peer-reviewed articles indexed in Scopus and SINTA published between 2020 and 2025. The review follows the PRISMA 2020 framework with inclusion criteria focusing on quantitative LCA studies and economic-environmental sustainability aspects. Literature was retrieved from Scopus, ScienceDirect, MDPI, SpringerLink, and SINTA databases using the keywords “banana peel”, “bioethanol”, “LCA”, and “sustainability”. The results indicate that pretreatment and distillation stages are the main contributors to energy consumption and greenhouse gas emissions, accounting for approximately 55–65% of total Global Warming Potential (GWP). However, the implementation of coproduct systems, such as converting residues into biogas or organic fertilizer, can reduce GWP by up to 30–40%. From an economic perspective, banana peel-based bioethanol production is financially viable at a medium scale when supported by renewable energy integration and centralized waste management systems. This study highlights the critical role of LCA as an evaluation tool for waste-based energy development and underscores the need for national standards for LCA methodologies in the bioenergy sector. To the best of our knowledge, this is the first comprehensive SLR integrating LCA and economic-environmental sustainability analysis for yellow kepok banana peel bioethanol, providing relevant insights for renewable energy policy and circular waste management in Indonesia.